Hubungan Minat Belajar IPA dengan Hasil Belajar Pada Mata Pelajaran IPA Kelas 5 Di SDN Sudimara Timur 4 Kota Tangerang - Nabilah Asyraf; Ferry Perdiansyah; Moh. Zamroni (Departement of Mathematics Education, 2023)
This study aims to determine the correlation between students' interest in learning Natural Sciences (IPA) and their learning outcomes in Grade 5 at SD Negeri Sudimara Timur 4, Kota Tangerang. The research design used is correlational research. The subjects of the study are 60 students from classes VA and VB at SD Negeri Sudimara Timur 4, with 30 students in each class. Data collection techniques include questionnaires and performance tests. The validity of the data is assessed using the correlation product-moment formula, while reliability is tested using the Cronbach's alpha formula. Data analysis employs the product-moment correlation formula. The results of the research indicate a significant correlation between students' interest in learning Natural Sciences and their learning outcomes. This is demonstrated by the calculated correlation coefficient (r) being greater than the tabled (critical) correlation coefficient (0.960 > 0.254) and the significance level being less than 0.05 (0.000 < 0.05). In other words, when students' interest in learning increases, their learning outcomes also tend to improve. From these findings, it can be concluded that there is a significant correlation between the variable of interest in learning and the variable of learning outcomes among Grade 5 students at SDN Sudimara Timur 4, Kota Tangerang.